Open lung approach ventilation abolishes the negative effects of respiratory rate in experimental lung injury. Issue 8 (25th April 2016) - Retamal, J.; Borges, J. B.; Bruhn, A.; Feinstein, R.; Hedenstierna, G.; Suarez‐Sipmann, F.; Larsson, A.
Abstract : Background: We recently reported that a high respiratory rate was associated with less inflammation than a low respiratory rate, but caused more pulmonary edema in a model of ARDS when an ARDSNet ventilatory strategy was used. We hypothesized that an open lung approach (OLA) strategy would neutralize the independent effects of respiratory rate on lung inflammation and edema. This hypothesis was tested in an ARDS model using two clinically relevant respiratory rates during OLA strategy. Methods: Twelve piglets were subjected to an experimental model of ARDS and randomized into two groups: LRR (20 breaths/min) and HRR (40 breaths/min). They were mechanically ventilated for 6 h according to an OLA strategy. We assessed respiratory mechanics, hemodynamics, and extravascular lung water (EVLW). At the end of the experiment, wet/dry ratio, regional histology, and cytokines were evaluated. Results: After the ARDS model was established, Cdyn, rs decreased from 21 ± 3.3 to 9.0 ± 1.8 ml/cmH2 O ( P < 0.0001). After the lung recruitment maneuver, Cdyn, rs increased to the pre‐injury value. During OLA ventilation, no differences in respiratory mechanics, hemodynamics, or EVLW were observed between groups. Wet/dry ratio and histological scores were not different between groups. Cytokine quantification was similar and showed a homogeneous distribution throughout the lung in both groups. Conclusion: Contrary to previous findings with the ARDSNet strategy, respiratory rate did not influence lung inflammatory response or pulmonary edema during OLA ventilation in experimental ARDS. This indicates that changing the respiratory rate when OLA ventilation is used will not exacerbate lung injury.